2014
DOI: 10.1038/cddis.2014.343
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Btk/Etk of prostate cancer cells by a novel dual inhibitor

Abstract: Btk and Etk/BMX are Tec-family non-receptor tyrosine kinases. Btk has previously been reported to be expressed primarily in B cells and has an important role in immune responses and B-cell malignancies. Etk has been shown previously to provide a strong survival and metastasis signal in human prostate cancer cells, and to confer androgen independence and drug resistance. While the role of Etk in prostate carcinogenesis is well established, the functions of Btk in prostate cancer have never been investigated, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 62 publications
1
50
0
Order By: Relevance
“…To further understand the biological function of Etk in chemoresistance of SCLC, we examined the literatures. A study showed that CTN06, a dual inhibitor of Btk and Etk, promoted autophagy in prostate cancer, which also exhibited increased sensitivity to docetaxel and implied a negative correlation between Etk and autophagy (19). Thus, we hypothesized that Etk modulated chemoresistance of SCLC by autophagy.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…To further understand the biological function of Etk in chemoresistance of SCLC, we examined the literatures. A study showed that CTN06, a dual inhibitor of Btk and Etk, promoted autophagy in prostate cancer, which also exhibited increased sensitivity to docetaxel and implied a negative correlation between Etk and autophagy (19). Thus, we hypothesized that Etk modulated chemoresistance of SCLC by autophagy.…”
Section: Discussionmentioning
confidence: 94%
“…Although it is difficult to reconcile the results of our study with those of the two discordant studies described above, we believe that the combined use of TEM, CLSM, and Western blotting to monitor autophagy, as well as the application of siRNAs to downregulate Etk and PRKRB4 in chemoresistant SCLC cell lines, provide adequate data to support our claims that downregulation of Etk or PFKFB4 could significantly inhibit autophagy in SCLC. In addition, the studies mentioned above that used prostate cancer cells and non-small cell lung cancer cells as the experiment models (19); thus, the discordant results suggest that in SCLC, PFKFB4 may modulate autophagy by mechanisms other than suppressing either ROS or p62 accumulation. Hence, it is critical to elucidate the molecule mechanisms by which PFKFB4 contributes to autophagy and present effective regimens to inhibit autophagy for improving chemosensitivity in SCLC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BTK is the prototype of this family [80]. TEC members are important players in the regulation of the immune system and have important functions in T cell activation, differentiation and cell signaling [81].…”
Section: Tec Protein Kinasementioning
confidence: 99%